Self-regulation, peer social support and instagram addiction in early single adults - Salsabila Najmidhia Budi (International Journal on Social Science, Economics and Art, 2023)
Instagram can give its users the opportunity to present themselves and make their mood more positive, but the desire to maintain this positive mood can lead to Instagram addictive behavior. There are several things that can influence the occurrence of Instagram addiction, one of which is self-regulation and peer support. The purpose of this study was to determine the effect of self-regulation and peer social support on social media addiction in early single adulthood. The sample used in this study was 96 single early adult respondents who had a tendency to be addicted to Instagram. The results of data analysis show that peer self-regulation and social support have an effect of 6.8% on Instagram addiction. Partially, only peer social support has no effect on Instagram addiction.